Identification of Landslide Vulnerability Levels in Songan B Village, Kintamani District, Bangli, Using the Wenner Geoelectric Resistivity Configuration Method - Suarbawa, Komang Ngurah; Paramarta, I.B. Alit; Arix Putra Wiguna, I Putu (BULETIN FISIKA, 2024)
Landslides are the movement of slope-forming material in the form of rocks, debris, soil, or mixed materials that move down or off the slope; this occurs due to high intensity rain on the sliding surface. This research aims to determine the level of landslide vulnerability in Songan B village, Kintamani Bangli sub-district, namely by knowing the structure of the soil layers in landslide-prone areas and knowing the coordinates and depth of the slip plane in the village using the Wenner configuration geoelectric method. Determination of the slip area is obtained based on the difference in resistivity values. The research used three different locations with four trajectories. Resistivity data processing was carried out using Res2dinv software. The interpretation results show that the structure of the soil layers in landslide-prone locations in Songan B Village, Kintamani District, Bangli at locations I, II, and III consist of clay, silt, sand, sandstone, basalt or granite, and andesite. Location I, with coordinates 115°25'1.28"E 8°12'59.92"S-115°25'0.78"E 8°12'58.79"S, there is a slip area with a depth of around 5 m. At location II with coordinates 115°25'6.62"E 8°13'9.14"S-115°25'8.68"E 8°13'9.03"S there is a slip area with a depth of 2-3 m. At location III track 1 with coordinates 115°25'25.45"E 8°13'36.22"S-115°25'28.15"E 8°13'37.77"S there is a slip area with a depth of 4-15 m. At location III track 2 with coordinates 115°25'26.28"E 8°13'36.06"S-115°25'28.43"E 8°13'36.88"S there is a slip plane with a depth of 3-8 m. The material that acts as a sliding plane on the four tracks is sandstone which has a resistivity value of 200-8000 ?m.